THE FEELING OF GENDER DISABILITY IN SIDDHARAMA’S REAL VACHANAS - Belale, Kumar; Chandrakath, K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the twelfth century, the Shiva Sharanas led their ideal married life and became guides for the future. The feeling of "Sharanas Sati Linga Pati" has been observed among the Veerashaiva devotees since the beginning. The vachana literature stands as a witness to this. The fact that they moved from worldly roles to spirituality is a fact that is evident from the life of the sharanas. They are examples of those who eat and fast and are celibate even after marriage. Siddharama, who is a very prominent Shiva Sharanas, has also mentioned this issue. The vachanas of the Sati-Pati feeling are special in Siddharama. Siddarama, who considers herself a woman and Kapila Siddha Mallikarjuna as a man, reminds us of the devotional Gajesha Masanayya and Urilingadeva. The pain of separation in a woman’s mind, the longing for Nallana’s arrival, the joy of the mind when Nallana appears, and the unity of each other are so beautifully expressed in words.